Genotoxic and mutagenic properties of Ni and NiO nanoparticles investigated by comet assay, γ‐H2AX staining, Hprt mutation assay and ToxTracker reporter cell lines. (15th December 2017) - Åkerlund, Emma; Cappellini, Francesca; Di Bucchianico, Sebastiano; Islam, Shafiqul; Skoglund, Sara; Derr, Remco; Odnevall Wallinder, Inger; Hendriks, Giel; Karlsson, Hanna L.
Abstract : Nickel (Ni) compounds are classified as carcinogenic to humans but the underlying mechanisms are still poorly understood. Furthermore, effects related to nanoparticles (NPs) of Ni have not been fully elucidated. The aim of this study was to investigate genotoxicity and mutagenicity of Ni and NiO NPs and compare the effect to soluble Ni from NiCl2 . We employed different models; i.e., exposure of (1) human bronchial epithelial cells (HBEC) followed by DNA strand break analysis (comet assay and γ‐H2AX staining); (2) six different mouse embryonic stem (mES) reporter cell lines (ToxTracker) that are constructed to exhibit fluorescence upon the induction of various pathways of relevance for (geno)toxicity and cancer; and (3) mES cells followed by mutagenicity testing ( Hprt assay). The results showed increased DNA strand breaks (comet assay) for the NiO NPs and at higher doses also for the Ni NPs whereas no effects were observed for Ni ions/complexes from NiCl2 . By employing the reporter cell lines, oxidative stress was observed as the main toxic mechanism and protein unfolding occurred at cytotoxic doses for all three Ni‐containing materials. Oxidative stress was also detected in the HBEC cells following NP‐exposure. None of these materials induced the reporter related to direct DNA damage and stalled replication forks. A small but statistically significant increase in Hprt mutations was observed for NiO but only at one dose. We conclude that Ni and NiO NPs show more pronounced (geno)toxic effects compared to Ni ions/complexes, indicating more serious health concerns. Environ. Mol. Mutagen. 59:211–222, 2018. © 2017 The Authors Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society